Battery Lifetime Extension Optimization in Integrated Energy System - Wu, Xingchen; Hua, Haochen; Wang, Yujie; Chen, Xingying; Wang, Rui (2023 IEEE International Conference on Energy Internet (ICEI), 2023)
The high investment and maintenance costs make it necessary to extend the lifetime of battery energy storage (BES) device in integrated energy system (IES). Different from existing works designing optimization techniques directly on BES, in this paper, the lifetime of BES is extended indirectly by optimizing the output power of gas turbines within the IES and the electricity purchasing from the external grid. The optimization issue is transformed into mixed integer quadratically constrained programming problem (MIQCP) and solved via solvers CPLEX and YALMIP toolbox in MATLAB. Simulation results indicate that compared with the strategy without extending the energy storage life, the throughput of BES decreased by 14.2%, effectively demonstrating that the proposed strategy in this paper can extend the battery lifetime.